Pengaruh Corporate Social Responsibility terhadap Harga Saham: Peran Moderasi Ukuran Komite Audit pada Badan Usaha Milik Negara(2019-2024) - Mualim Muslimin; Emillia Nurdin; Nur Asni (Politeknik Ganesha Medan, 2026)
This study aims to assess the extent to which Corporate Social Responsibility (CSR) affects a company's stock price, as well as to examine the role of Good Corporate Governance (GCG) as a moderating variable in this relationship. This study focuses on State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange for the 2019–2024 period. The study population consisted of 70 companies, and sampling was conducted using a purposive sampling method, resulting in 25 companies being included. Based on the results of the model selection test, the appropriate model used in this study is the Random Effects Model (REM). The findings indicate that Corporate Social Responsibility (CSR), with a proxy for the natural logarithm of CSR expenditures, has an impact on stock prices, where increased CSR expenditures provide a positive signal to investors regarding the company's reputation and attractiveness. Furthermore, Good Corporate Governance (GCG), with a proxy for the number of audit committee members, is proven to strengthen the relationship between CSR and stock prices. Audit committees contribute to improving the quality of oversight, transparency, and reporting, thereby strengthening positive investor perceptions. Empirical results show that state-owned companies must pay attention to the size of CSR expenditures to influence share prices and consider the number of audit committees as a factor that can strengthen the relationship between Corporate Governance and share prices.